Slurry for secondary battery, positive electrode for secondary battery, and secondary battery
By using inorganic particles with metals other than alkali metals and alkaline earth metals as main components, combined with an appropriate amount of alkali metals and alkaline earth metals, the problem of poor dispersion of materials in the slurry for secondary batteries is solved, and the problem of poor dispersion of materials in the slurry for secondary batteries is achieved. Battery internal resistance is reduced and performance is improved.
Patent Information
- Application Number
- CN201980058571.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-09-18
- Filing Date
- 2019-08-29
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2039-08-29
AI Technical Summary
It is difficult to achieve good dispersion of the material when the existing slurry for secondary batteries is formed, which affects the productivity and performance of the battery.
Inorganic particles with metals other than alkali metals and alkaline earth metals as main components, combined with an appropriate amount of alkali metals and alkaline earth metals as the main components of the slurry for secondary batteries, so as to improve the dispersion of inorganic particles. and viscosity of the slurry.
By improving the dispersion of inorganic particles, a high-quality intermediate layer is formed, the internal resistance of the battery is reduced, and the input and output characteristics and overall performance of the battery are improved.
Smart Images

Figure CN112655102B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a slurry for a secondary battery, a positive electrode for a secondary battery, and a secondary battery. Background Art
[0002] In the past, various slurries such as composite material slurry for forming a composite material layer of an electrode and intermediate layer slurry for forming an intermediate layer (protective layer) on the surface of a positive electrode collector were widely used in the manufacture of secondary batteries. Patent document 1 discloses a positive electrode for a secondary battery having an intermediate layer with aluminum oxide as the main component formed between the collector and the composite material layer. The intermediate layer is formed by applying an intermediate layer slurry containing aluminum oxide, a conductive material and a binding material to the surface of the collector and drying the coating.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2016-127000 Summary of the invention
[0006] However, in order to stably form a high-quality coating (layer) using a secondary battery slurry, it is important to make the dispersibility of the material (constituent material of the layer) contained in the slurry present a good state. The purpose of this application is to provide a secondary battery slurry with good dispersibility of the material without using additives such as those that may damage the productivity and performance of the battery. In addition, a high-quality intermediate layer is formed on the surface of the positive electrode collector to improve the battery performance.
[0007] A secondary battery slurry according to one embodiment of the present application comprises inorganic particles, a binder and a dispersion medium, wherein the inorganic particles are composed of a metal compound having a metal other than an alkali metal and an alkaline earth metal as a main component and containing 0.001 to 2% by mass of an alkali metal and 0.1 to 4% by mass of an alkaline earth metal.
[0008] A secondary battery positive electrode as one embodiment of the present application comprises a current collector, an intermediate layer formed on at least one surface of the current collector, and a composite material layer formed on the intermediate layer. The intermediate layer comprises inorganic particles, a conductive material, and a binder, wherein the inorganic particles are composed of a metal compound having a metal other than an alkali metal and an alkaline earth metal as a main component and containing 0.001 to 2% by mass of an alkali metal and 0.1 to 4% by mass of an alkaline earth metal.
[0009] A secondary battery as one embodiment of the present application includes the above-mentioned positive electrode, a negative electrode, and an electrolyte.
[0010] According to the secondary battery slurry as one solution of the present application, the dispersibility of materials such as inorganic particles contained in the slurry can be improved without using additives such as those that may damage the productivity and performance of the battery. In addition, the secondary battery having the positive electrode as one solution of the present application has low internal resistance and excellent input-output characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a cross-sectional view of a secondary battery as an example of an embodiment.
[0012] Figure 2 It is a cross-sectional view of a positive electrode as an example of an embodiment. DETAILED DESCRIPTION
[0013] In order to stably form a high-quality intermediate layer using secondary battery slurry, the dispersibility of the inorganic particles contained in the slurry must be in a good state. The inventors and others have conducted in-depth research on this topic and found that by using inorganic particles composed of metal compounds with metals other than alkali metals and alkaline earth metals as the main component and containing at least one of 0.001 to 2% by mass of alkali metals and 0.1 to 4% by mass of alkaline earth metals, the viscosity of the slurry is reduced and the dispersibility of the inorganic particles is improved. The secondary battery slurry described in the present application has good coating properties and can form a high-quality intermediate layer.
[0014] It should be noted that in the case of an internal short circuit in the battery, the positive electrode collector with aluminum as the main component and the lithium-containing transition metal oxide as the positive electrode active material may undergo an oxidation-reduction reaction, resulting in a large amount of heat release. By providing an intermediate layer with the above-mentioned inorganic particles as the main component between the positive electrode collector and the positive electrode composite material layer, the positive electrode collector and the positive electrode composite material layer can be separated to suppress heat release when an abnormality occurs. By making the intermediate layer contain insulating inorganic particles, there is a concern about the increase in internal resistance of the battery during normal battery charging and discharging. The high-quality intermediate layer described in this application refers to an intermediate layer that uses inorganic particles containing a metal compound of at least one of 0.001 to 2 mass% of an alkali metal and 0.1 to 4 mass% of an alkaline earth metal as an intermediate layer, thereby alleviating the increase in internal resistance caused by the inclusion of an intermediate layer in the battery.
[0015] Hereinafter, an example of an embodiment of the secondary battery slurry, the secondary battery positive electrode, and the secondary battery described in the present application is described in detail. Hereinafter, as an example of an embodiment, an intermediate layer slurry for forming an intermediate layer on the surface of a positive electrode collector is illustrated, but the secondary battery slurry described in the present application is not limited thereto.
[0016] In addition, the following is a detailed description of an example of an embodiment of a positive electrode for a secondary battery and a secondary battery described in the present application. The following example shows a cylindrical battery in which a wound electrode body 14 is housed in a cylindrical battery case, but the electrode body is not limited to a wound type, and can be a stacked type in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked one by one through a separator. In addition, the secondary battery described in the present application can be a square battery with a square metal shell, a coin-shaped battery with a coin-shaped metal shell, etc., or a laminated battery with an outer packaging body composed of a laminated sheet comprising a metal layer and a resin layer.
[0017] Figure 1 1 is a cross-sectional view of a secondary battery 10 as an example of an embodiment. Figure 1 As shown in the example, the secondary battery 10 includes an electrode body 14, an electrolyte, and a battery case 15 for accommodating the electrode body 14 and the electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a winding structure in which the positive electrode 11 and the negative electrode 12 are wound with the separator 13 interposed therebetween. The battery case 15 is composed of an outer packaging can 16 with a bottom cylindrical shape and a sealing body 17 that seals the opening of the outer packaging can 16. It should be noted that the secondary battery 10 can be a secondary battery using an aqueous electrolyte or a secondary battery using a non-aqueous electrolyte. The following description will be given in the form of a non-aqueous electrolyte secondary battery such as a lithium ion battery using a non-aqueous electrolyte.
[0018] The non-aqueous electrolyte comprises a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous solvent may use, for example, esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. The non-aqueous solvent may contain halogen-substituted bodies such as fluoroethylene carbonate obtained by replacing at least a portion of hydrogen in these solvents with halogen atoms such as fluorine. It should be noted that the non-aqueous electrolyte is not limited to a liquid electrolyte and may be a solid electrolyte. The electrolyte salt may use lithium salts such as LiPF6.
[0019] The secondary battery 10 includes insulating plates 18 and 19 disposed above and below the electrode body 14, respectively. Figure 1 In the example shown, the positive electrode lead 20 attached to the positive electrode 11 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 attached to the negative electrode 12 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the bottom plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the lid 27 electrically connected to the bottom plate 23 serves as a positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as a negative terminal.
[0020] The outer can 16 is a metal container in a cylindrical shape with a bottom. A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness of the battery interior. The outer can 16 is formed with a groove 22 in which a part of the side surface bulges inward and is used to support the sealing body 17. The groove 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface.
[0021] The sealing body 17 has a structure in which a bottom plate 23, a lower valve plug 24, an insulating component 25, an upper valve plug 26 and a cover body 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating component 25 are electrically connected to each other. The lower valve plug 24 and the upper valve plug 26 are connected to each other at their respective central portions, and the insulating component 25 is sandwiched between their respective edge portions. If the internal pressure of the battery rises due to abnormal heating, the lower valve plug 24 is deformed and broken in a manner that pushes the upper valve plug 26 toward the cover body 27 side, thereby blocking the circuit between the lower valve plug 24 and the upper valve plug 26. If the internal pressure rises further, the upper valve plug 26 breaks and gas is discharged from the opening of the cover body 27.
[0022] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , particularly the positive electrode 11 and the intermediate layer slurry for forming the intermediate layer 32 of the positive electrode 11 will be described in detail.
[0023] [positive electrode]
[0024] Figure 2 1 is a cross-sectional view of a positive electrode 11 as an example of an embodiment. Figure 2 As shown in the example, the positive electrode 11 includes a positive electrode collector 30, an intermediate layer 32 formed on at least one surface of the positive electrode collector 30, and a positive electrode composite material layer 31 formed on the intermediate layer 32. The intermediate layer 32 is preferably formed on both sides of the positive electrode collector 30. The positive electrode composite material layer 31 contains a positive electrode active material, a conductive material, and a binder, and is formed on both sides of the positive electrode collector 30 via the intermediate layer 32. It should be noted that there may be an area on the surface of the positive electrode collector 30 where the intermediate layer 32 is not formed, and in this area, the positive electrode composite material layer 31 is directly formed on the positive electrode collector 30.
[0025] The positive electrode 11 is manufactured by coating the intermediate layer slurry on both sides of the positive electrode collector 30, drying the coating to form the intermediate layer 32, and then forming the positive electrode composite material layer 31 on the intermediate layer 32. The positive electrode composite material layer 31 is formed on both sides of the positive electrode collector 30 through the intermediate layer 32 by coating the positive electrode composite material slurry containing a positive electrode active material, a conductive material, and a binding material on the intermediate layer 32, drying the coating, and then compressing the coating.
[0026] As the positive electrode current collector 30, a foil of a metal such as aluminum or an aluminum alloy that is stable within the potential range of the positive electrode 11, a thin film of such a metal disposed on the surface layer, or the like can be used. The aluminum content rate in the positive electrode current collector 30 is 50% or more, preferably 70% or more, and more preferably 80% or more, relative to the mass of the current collector. A suitable positive electrode current collector 30 is a metal foil formed of aluminum or an aluminum alloy and has a thickness of 5 μm to 20 μm.
[0027] As the positive electrode active material, a lithium-containing transition metal oxide containing transition metal elements such as Co, Mn, Ni, etc. can be used. Examples of the lithium-containing transition metal oxide include Li x CoO2, Li x NiO2, Li x MnO2, Li x Co y Ni 1-y O2, Li x Co y M 1- y O z 、Li x Ni 1-y M y O z 、Li x Mn2O4, Li x Mn 2-y M y O4, LiMPO4, Li2MPO4F (M: at least one of Na, Mg, Sc, Y, Mn, Fe, Co, Ni, Cu, Zn, Al, Cr, Pb, Sb, B; 0 < x ≤ 1.2, 0 < y ≤ 0.9, 2.0 ≤ z ≤ 2.3), etc. They can be used alone or in combination of multiple kinds.
[0028] Examples of the conductive material contained in the positive electrode composite material layer 31 include carbon materials such as carbon black (CB), acetylene black (AB), Ketjen black, and graphite. Examples of the binder material contained in the positive electrode composite material layer 31 include fluorine-based resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVdF); polyacrylonitrile (PAN), polyimide-based resins, acrylic-based resins, polyolefin-based resins, etc. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salts, polyethylene oxide (PEO), etc. They can be used alone or in combination of multiple kinds.
[0029] As described above, the intermediate layer 32 is sandwiched between the positive electrode collector 30 and the positive electrode composite material layer 31. The intermediate layer 32 includes inorganic particles 35 and a binder, and is composed of the inorganic particles 35 as a main component. Here, the main component refers to the component with the largest mass among the constituent materials of the intermediate layer 32. The content of the inorganic particles 35 is preferably 70 to 99% by mass, more preferably 80 to 98% by mass, and particularly preferably 90 to 97% by mass relative to the mass of the intermediate layer 32. The thickness of the intermediate layer 32 is not particularly limited, and is preferably 1 μm to 10 μm or 1 μm to 5 μm.
[0030] The inorganic particles 35 are composed of a metal compound having a metal other than an alkali metal and an alkaline earth metal as a main component and containing 0.001 to 2 mass % of an alkali metal and 0.1 to 4 mass % of an alkaline earth metal.
[0031] The inorganic particles 35 are composed of a metal compound having a metal other than an alkali metal and an alkaline earth metal as a main component and containing 0.001 to 2% by mass of an alkali metal (Li, Na, K, Rb, Sc, Fr). By making the metal compound contain 0.001 to 2% by mass of an alkali metal, a high-quality intermediate layer 32 is formed, and the internal resistance of the battery is reduced. The content of the alkali metal is 0.001 to 2% by mass relative to the mass of the inorganic particles 35, preferably 0.005 to 1.5% by mass, and more preferably 0.01 to 1% by mass. Suitable alkali metals contained in the metal compound are Na and K. The metal compound may be added with one alkali metal or with two or more alkali metals. The inorganic particles 35 containing 0.001 to 2% by mass of an alkali metal may further contain 0.1 to 4% by mass of an alkaline earth metal.
[0032] The metal compound constituting the inorganic particles 35 is preferably a metal compound having an oxidizing power lower than that of the lithium-containing transition metal oxide. The metal compound contains, as a metal element other than alkali metals and alkaline earth metals, at least one selected from, for example, Mn, Si, Ti and Al. The metal compound is at least one selected from, for example, metal oxides and metal hydroxides. Specific examples of suitable metal compounds (oxides and hydroxides) include manganese oxide, silicon dioxide (silica), titanium dioxide (titania), aluminum oxide (alumina), aluminum hydroxide, boehmite, etc. Among them, it is preferred to use at least one selected from aluminum oxide, aluminum hydroxide and boehmite as the main component.
[0033] When the metal compound is, for example, aluminum oxide, aluminum hydroxide, or boehmite containing 0.001 to 2 mass% of an alkali metal, the main component (the component with the largest mass) of the metal element contained in the compound is Al. When the metal compound is, for example, silicon dioxide containing 0.001 to 2 mass% of an alkali metal, the main component of the metal element contained in the compound is Si. When the metal compound is, for example, titanium dioxide containing 0.001 to 2 mass% of an alkali metal, the main component of the metal element contained in the compound is Ti. A suitable example of the metal compound is aluminum oxide, aluminum hydroxide, or boehmite containing 0.01 to 1 mass% of Na or K relative to the mass of the inorganic particles 35.
[0034] The inorganic particles 35 are composed of a metal compound having a metal other than an alkali metal and an alkaline earth metal as a main component and containing 0.1 to 4 mass % of an alkaline earth metal (Be, Mg, Ca, Sr, Ba, Ra). The inorganic particles 35 containing 0.1 to 4 mass % of an alkaline earth metal may further contain 0.001 to 2 mass % of an alkali metal.
[0035] The addition of alkaline earth metals helps to form a high-quality intermediate layer 32. The content of alkaline earth metals is 0.1 to 4% by mass, preferably 0.2 to 3% by mass, and more preferably 0.5 to 2% by mass relative to the mass of the inorganic particles 35. Suitable alkaline earth metals contained in the metal compound are Mg, Ca, Sr, and Ba. The metal compound may be added with one alkaline earth metal or with two or more alkaline earth metals.
[0036] The metal compound is, for example, aluminum oxide, aluminum hydroxide, or boehmite containing 0.01 to 1 mass % of Na or K and 0.1 to 4 mass % of Mg, Ca, Sr, or Ba relative to the mass of the inorganic particles 35 .
[0037] The volume-based median particle size (D50) of the inorganic particles 35 is, for example, 0.05 μm to 2 μm, preferably 0.1 μm to 1 μm. The median particle size of the inorganic particles 35 is the particle size at which the volume cumulative value reaches 50% in the particle size distribution measured by the laser diffraction scattering method. In addition, the aspect ratio of the inorganic particles 35 can be greater than 2. It should be noted that the intermediate layer 32 may include two or more inorganic particles 35 with different compositions, particle sizes, etc., and may also include inorganic particles other than inorganic particles 35 and conductive materials 36 within the scope that does not impair the purpose of the present application.
[0038] The intermediate layer 32 may include metal phosphorus oxide particles. Specific examples include Li3PO4, LiPON, Li2HPO4, LiH2PO4, Na3PO4, Na2HPO4, NaH2PO4, Zr3(PO4)4, Zr(HPO4)2, HZr2(PO4)3, K3PO4, K2HPO4, KH2PO4, Ca3(PO4)2, CaHPO4, Mg3(PO4)2, MgHPO4, LiCl-Li5P3O 10 、LiCl-Li7P5O 16 , LiCl-LiPO3, LiCl-Li2O-P2O5, Li2O-P2O5, AgI-AgPO3, CuI-CuPO3, PbF2-MnF2-Al(PO4)3, AgI-Ag2O-P2O5, AlPO4, Mn3(PO4)2·3H2O, etc. Among them, preferably at least one selected from lithium phosphate (Li3PO4 particles), lithium hydrogen phosphate (Li2HPO4), aluminum phosphate (AlPO4) and manganese phosphate hydrate (Mn3(PO4)2·3H2O).
[0039] The binder included in the intermediate layer 32 can use the same type of conductive material as that used in the positive electrode composite material layer 31, such as fluororesins such as PTFE and PVdF, PAN, polyimide resins, acrylic resins, polyolefin resins, etc. Among them, PVdF is preferred. The content of the binder is preferably 0.1 to 10% by mass relative to the mass of the intermediate layer 32, and more preferably 1 to 5% by mass. The content of the inorganic particles 35, the conductive material 36, and the binder in the intermediate layer 32 can be obtained by cross-sectional observation and element mapping of the intermediate layer 32 using a scanning electron microscope (SEM) or a transmission electron microscope (TEM).
[0040] As described above, the intermediate layer 32 can be formed by applying an intermediate layer slurry containing the constituent materials of the intermediate layer 32 to the surface of the positive electrode current collector 30 and drying the coating. The intermediate layer slurry is applied by a conventionally known method. The intermediate layer 32 is applied to the surface of the positive electrode current collector 30 at a density of, for example, 0.1 g / m 2 ~20g / m 2 to form a surface density.
[0041] The intermediate layer slurry preferably contains a conductive material 36 for forming a conductive path in the intermediate layer 32. During normal battery charge and discharge, it is preferable to alleviate the insulation performance caused by the intermediate layer 32 containing inorganic particles 35. In order to alleviate the insulation due to the inorganic particles 35, the intermediate layer 32 preferably contains a conductive material 36.
[0042] The conductive material 36 included in the intermediate layer 32 can use the same type of conductive material as the conductive material used in the positive electrode composite material layer 31, such as conductive particles such as CB, AB, Ketjen black, and graphite. The conductive material 36 is attached to the surface of the inorganic particles 35 by means of a binder to form a conductive path in the intermediate layer 32. The content of the conductive material 36 is preferably 0.5 to 10% by mass, more preferably 1 to 5% by mass relative to the mass of the intermediate layer 32. If the content of the conductive material 36 is within this range, a good conductive path is formed in the intermediate layer 32.
[0043] The intermediate layer slurry is a secondary battery slurry containing inorganic particles 35, a binder and a dispersion medium. When the intermediate layer 32 contains a conductive material 36, the intermediate layer slurry also contains a conductive material 36. As described above, the inorganic particles 35 are composed of a metal compound having a metal other than an alkali metal and an alkaline earth metal as a main component and containing at least one of 0.001 to 2% by mass of an alkali metal and 0.1 to 4% by mass of an alkaline earth metal. By adding 0.001 to 2% by mass of an alkali metal to the metal compound, the dispersibility of the inorganic particles 35 is improved, the viscosity of the slurry is reduced, and the coating property of the slurry is improved. As a result, a high-quality intermediate layer 32 can be formed, and the battery performance is improved.
[0044] The metal compound containing 0.001 to 2 mass % of an alkali metal may further contain 0.1 to 4 mass % of an alkaline earth metal.
[0045] Suitable elements and suitable contents of alkali metals and alkaline earth metals are as described above. The metal compound is, for example, at least one selected from metal oxides and metal hydroxides, and specifically preferably contains at least one selected from aluminum oxide, aluminum hydroxide and boehmite as a main component.
[0046] The inorganic particles 35 are manufactured by, for example, impregnating particles of a metal compound containing metal elements such as Mn, Si, Ti, and Al in an aqueous solution of an alkali metal compound such as an aqueous sodium hydroxide solution or an aqueous potassium hydroxide solution, and then drying and calcining the particles. In addition, when an alkaline earth metal is added to the metal compound, the particles are manufactured by mixing powders of alkaline earth metal compounds such as magnesium oxide and calcium oxide with particles of a metal compound containing metal elements such as Mn, Si, Ti, and Al, and then calcining the mixed particles. The calcination is performed, for example, at a temperature of 1200 to 1600° C. in the atmosphere.
[0047] The solid content concentration of the intermediate layer slurry is preferably 30 to 50% by mass, more preferably 35 to 45% by mass. If the solid content concentration is within this range, it is easy to form an intermediate layer 32 with a thickness of 1 μm to 10 μm. When the solid content concentration is less than 30% by mass, the viscosity of the slurry decreases, but production problems such as the drying of the coating film taking a long time may occur. The viscosity of the intermediate layer slurry measured using a B-type viscometer (25°C) is preferably 30 to 80 cP or 40 to 70 cP. By using inorganic particles 35, a viscosity of 40 to 70 cP can be achieved under conditions where the solid content concentration is 30 to 50% by mass.
[0048] The dispersion medium of the intermediate layer slurry is not particularly limited as long as it is a liquid that can be volatilized and removed, and can be appropriately changed according to the type of the bonding material, etc. The dispersion medium can use, for example, an organic solvent or water that is the same as the dispersion medium used in the composite material slurry. The dispersion medium can be a liquid that does not dissolve the inorganic particles 35 and the bonding material, or it can be a liquid that does not dissolve the inorganic particles 35 but dissolves the bonding material. An example of a suitable dispersion medium is N-methyl-2-pyrrolidone (NMP).
[0049] The slurry for the intermediate layer can be prepared by adding a mixed powder of inorganic particles 35 and a bonding material to a dispersion medium and mixing using a conventionally known stirring device. Alternatively, each powder can be added to the dispersion medium separately, or the dispersion medium can be added to the mixed powder. The amount of inorganic particles 35 added is preferably 70 to 99% by mass, more preferably 80 to 98% by mass, and particularly preferably 90 to 97% by mass relative to the total mass of the solid component. When the solid component substantially only includes inorganic particles 35, conductive material 36 and bonding material, the total amount of conductive material 36 and bonding material added is 1 to 30% by mass, particularly preferably 3 to 10% by mass.
[0050] [negative electrode]
[0051] The negative electrode 12 includes a negative electrode current collector and a negative electrode composite material layer formed on at least one surface of the current collector. The negative electrode current collector may be made of a foil of a metal such as copper or a copper alloy that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode composite material layer preferably includes a negative electrode active material and a binding material, and is formed on both sides of the negative electrode current collector. The negative electrode 12 may be manufactured by coating a negative electrode composite material slurry including a negative electrode active material, a binding material, etc. on the negative electrode current collector, drying the coating, and then rolling to form a negative electrode composite material layer on both sides of the current collector.
[0052] As the negative electrode active material, there is no particular limitation as long as it is a material that can reversibly absorb and release lithium ions, and carbon materials such as graphite are generally used. Graphite can be natural graphite such as flaky graphite, block graphite, and earthy graphite; any of block artificial graphite, graphitized mesophase carbon microbeads, and other artificial graphites. In addition, as the negative electrode active material, metals such as Si and Sn that alloy with Li; metal compounds containing Si, Sn, and the like, lithium-titanium composite oxides, and the like can be used. SiO x The Si-containing compound represented by (0.5≤x≤1.6) can be used together with a carbon material such as graphite.
[0053] The binder included in the negative electrode composite material layer uses fluororesins such as PTFE and PVdF, PAN, polyimide, acrylic resin, polyolefin, etc., and preferably uses styrene-butadiene rubber (SBR) as in the case of the positive electrode 11. In addition, the negative electrode composite material layer may include CMC or its salt, polyacrylic acid (PAA) or its salt, PVA, etc. The negative electrode composite material layer includes, for example, SBR and CMC or its salt.
[0054] [Separator]
[0055] The separator 13 may be a porous sheet having ion permeability and insulation. Specific examples of the porous sheet include microporous films, woven fabrics, nonwoven fabrics, etc. The material of the separator is preferably polyolefins such as polyethylene and polypropylene, cellulose, etc. The separator 13 may be a single-layer structure or a laminated structure. In addition, a resin layer having high heat resistance such as an aromatic polyamide resin or a filler layer containing a filler of an inorganic compound may be provided on the surface of the separator 13.
[0056] Example
[0057] Hereinafter, the present application will be further described in detail by way of examples, but the present application is not limited to these examples.
[0058] <Example 1>
[0059] [Production of positive electrode]
[0060] After adding aluminum oxide (Al2O3) particles to a sodium hydroxide (NaOH) aqueous solution and stirring, the particles are dried and fired at 1500°C × 2 hours in the atmosphere to produce Al2O3 particles containing 0.001% by mass of Na relative to the total mass of the particles. Next, 95 parts by mass of the Al2O3 particles, 2 parts by mass of acetylene black (AB) and 3 parts by mass of polyvinylidene fluoride (PVdF) are mixed to prepare an intermediate layer slurry with a solid content concentration of 40% by mass using N-methyl-2-pyrrolidone (NMP) as a dispersion medium. The slurry is applied to both sides of a positive electrode collector formed of aluminum foil with a thickness of 15 μm, and the coating is dried to form an intermediate layer with a thickness of 3 μm.
[0061] The Na content in the Al2O3 particles was measured by ICP emission analysis. In addition, the dispersibility of the Al2O3 particles and AB particles in the intermediate layer slurry was good, and the viscosity of the intermediate layer slurry (25°C) was 60 cP. The viscosity of the slurry was measured using a B-type viscometer at 20 rpm.
[0062] As the positive electrode active material, LiNi 0.5 Co 0.2 Mn 0.3 A lithium-containing transition metal oxide shown in O2. The positive electrode active material, AB and PVdF are mixed at a solid content mass ratio of 97:2:1 to prepare a positive electrode composite material slurry using NMP as a dispersion medium. Next, the positive electrode composite material slurry is applied to both sides of the positive electrode collector formed with an intermediate layer, and after the coating film is dried, the coating film is compressed to form a positive electrode composite material layer on both sides of the collector through the intermediate layer. The collector is cut into a specified electrode size to produce a positive electrode.
[0063] [Production of negative electrode]
[0064] The graphite powder, sodium salt of CMC and dispersion of SBR were mixed at a solid content mass ratio of 98.7:0.7:0.6 to prepare a negative electrode composite material slurry using water as a dispersion medium. Next, the negative electrode composite material slurry was applied to both sides of a negative electrode collector formed of copper foil, and after the coating was dried, the coating was compressed to form a negative electrode composite material layer on both sides of the collector. The collector was cut into a specified electrode size to produce a negative electrode.
[0065] [Preparation of non-aqueous electrolyte]
[0066] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) were mixed at a volume ratio of 3:3:4. LiPF6 was dissolved in the mixed solvent at a concentration of 1.2 mol / L to prepare a non-aqueous electrolyte.
[0067] [Battery production]
[0068] An aluminum lead is installed on the positive electrode, and a nickel lead is installed on the negative electrode, and the positive electrode and the negative electrode are wound into a spiral shape through a polyethylene separator to produce a wound electrode body. The electrode body is accommodated in a bottomed cylindrical battery case body with an outer diameter of 18.2 mm and a height of 65 mm, and after the non-aqueous electrolyte is injected, the opening of the battery case body is sealed with a gasket and a sealing body to produce a cylindrical non-aqueous electrolyte secondary battery.
[0069] [Measurement of DC-IR (direct current resistance)]
[0070] The above-mentioned battery was measured according to the following procedures. The evaluation results are shown in Table 1 (the same applies to the following Examples and Comparative Examples).
[0071] Under a temperature environment of 25°C, the battery was charged at a constant current of 0.3C until the battery voltage reached 4.35V, then charged at a constant voltage until the current value reached 0.05C, and then discharged at a constant current of 0.3C to a SOC of 50%. Next, the voltage values when discharge currents of 0A, 0.1A, 0.5A, and 1.0A were applied for 10 seconds were obtained. DC-IR was calculated from the absolute value of the slope when the voltage value after 10 seconds was linearly approximated with respect to each discharge current value using the least squares method.
[0072] <Example 2>
[0073] In the preparation of the intermediate layer slurry, except that the Na content in the Al 2 O 3 particles was changed to 0.02 mass %, a positive electrode and a secondary battery were produced in the same manner as in Example 1, and their performance was evaluated.
[0074] <Example 3>
[0075] In the preparation of the intermediate layer slurry, a sodium hydroxide (NaOH) aqueous solution was mixed with magnesium oxide (MgO) particles and sintered in the atmosphere at 1500°C for 2 hours to add 0.02 mass % Na and 0.5 mass % Mg. In addition, a positive electrode and a secondary battery were prepared using the same method as in Example 2, and performance was evaluated.
[0076] <Example 4>
[0077] In the preparation of the intermediate layer slurry, Al2O3 particles containing 0.1 mass % Na and 3 mass % Mg were used instead of the inorganic particles used in Example 3. The positive electrode and secondary battery were made by the same method as in Example 3, and the performance was evaluated.
[0078] <Example 5>
[0079] In the preparation of the intermediate layer slurry, Al2O3 particles containing 1 mass % Na and 2 mass % Mg were used instead of the inorganic particles used in Example 3. A positive electrode and a secondary battery were prepared and the performance was evaluated using the same method as in Example 3. It should be noted that K was added to Al2O3 by using a potassium hydroxide (KOH) aqueous solution instead of a NaOH aqueous solution.
[0080] <Example 6>
[0081] In the preparation of the intermediate layer slurry, Al2O3 particles containing 1 mass % K and 2 mass % Mg were used instead of the inorganic particles used in Example 3. A positive electrode and a secondary battery were prepared and the performance was evaluated in the same manner as in Example 3. It should be noted that K was added to Al2O3 by using a potassium hydroxide (KOH) aqueous solution instead of a NaOH aqueous solution.
[0082] <Example 7>
[0083] In the preparation of the intermediate layer slurry, Al2O3 particles containing 2 mass % Na and 4 mass % Ca were used instead of the inorganic particles used in Example 3. A positive electrode and a secondary battery were prepared and the performance was evaluated in the same manner as in Example 3. It should be noted that Ca was added to Al2O3 by using calcium oxide (CaO) instead of MgO.
[0084] <Example 8>
[0085] In the preparation of the intermediate layer slurry, a positive electrode and a secondary battery were prepared by the same method as in Example 1, except that boehmite (AlOOH) particles were used instead of Al2O3 particles and the Na content was set to 1 mass %, and the performance was evaluated.
[0086] <Example 9>
[0087] A positive electrode and a secondary battery were produced in the same manner as in Example 8, except that aluminum hydroxide (Al(OH) 3 ) particles were used instead of AlOOH particles in the preparation of the intermediate layer slurry, and performance evaluation was performed.
[0088] <Example 10>
[0089] In the preparation of the intermediate layer slurry, titanium oxide (TiO 2 ) particles were used instead of Al 2 O 3 particles, and the Na content was set to 0.1 mass %. A positive electrode and a secondary battery were prepared by the same method as in Example 1, and performance was evaluated.
[0090] <Example 11>
[0091] In the preparation of the intermediate layer slurry, a sodium hydroxide (NaOH) aqueous solution was mixed with magnesium oxide (MgO) particles and sintered in the atmosphere at 1500°C for 2 hours to add 0.1 mass % Na and 0.5 mass % Mg. In addition, the positive electrode and secondary battery were made using the same method as in Example 10, and the performance was evaluated.
[0092] <Example 12>
[0093] In the preparation of the intermediate layer slurry, magnesium hydroxide (Mg(OH)2) was mixed instead of NaOH, and the mixture was sintered in the atmosphere at 1500°C for 2 hours to produce Al2O3 particles containing 2.0 mass% Mg relative to the total mass of the particles. In addition, the positive electrode and secondary battery were produced using the same method as in Example 1, and their performance was evaluated.
[0094] <Comparative Example 1>
[0095] A positive electrode and a secondary battery were produced in the same manner as in Example 1 except that an alkali metal and an alkaline earth metal were not added to the Al 2 O 3 particles in the preparation of the intermediate layer slurry.
[0096] <Comparative Example 2>
[0097] A positive electrode and a secondary battery were produced in the same manner as in Example 1 except that no alkali metal or alkaline earth metal was added to the TiO 2 particles in the preparation of the intermediate layer slurry.
[0098] [Table 1]
[0099]
[0100] From the results shown in Table 1, it can be understood that the viscosity of the intermediate layer slurry of the embodiment is lower than that of the slurry of Comparative Example 1 with the same solid content concentration, and the dispersibility of the inorganic particles is excellent. In other words, it can be considered that by adding a predetermined concentration of alkali metal to the metal compound particles as the main material, the dispersibility of the inorganic particles is greatly improved and the viscosity of the slurry is reduced. In addition, the DC-IR of the battery of the embodiment is lower than that of the battery of Comparative Example 1. It can be considered that by using a slurry with excellent dispersibility of inorganic particles to form an intermediate layer, a high-quality intermediate layer is formed, and the DC-IR of the battery is reduced.
[0101] Description of Reference Numerals
[0102] 10 Secondary batteries
[0103] 11 Positive electrode
[0104] 12 Negative electrode
[0105] 13 Divider
[0106] 14 Electrode body
[0107] 15 Battery housing
[0108] 16 Outer can
[0109] 17 Sealing body
[0110] 18, 19 Insulation board
[0111] 20 Positive lead
[0112] 21 Negative lead
[0113] 22 Groove
[0114] 23 Base Plate
[0115] 24 Lower valve plug
[0116] 25 Insulation parts
[0117] 26 Upper valve plug
[0118] 27 Cover
[0119] 28 Gasket D
[0120] 30 Positive electrode collector
[0121] 31. Positive electrode composite material layer
[0122] 32 Middle Layer
[0123] 35 Inorganic particles
[0124] 36 Conductive materials
Claims
1. A positive electrode for a secondary battery, comprising a current collector, an intermediate layer formed on at least one surface of the current collector, and a composite material layer formed on the intermediate layer, The intermediate layer comprises inorganic particles, conductive materials and bonding materials. The inorganic particles are composed of a metal compound including at least one selected from the group consisting of Mn and Ti, and further containing 0.001 to 2 mass % of an alkali metal and 0.1 to 4 mass % of an alkaline earth metal.
2. The positive electrode for a secondary battery according to claim 1, wherein The metal compound is at least one selected from metal oxides and metal hydroxides.
3. The positive electrode for a secondary battery according to claim 1, wherein The metal compound includes at least one selected from manganese oxide and titanium dioxide. 4 . A secondary battery comprising the positive electrode for a secondary battery according to claim 1 , a negative electrode, and an electrolyte.
5. A positive electrode for a secondary battery, comprising a current collector, an intermediate layer formed on at least one surface of the current collector, and a composite material layer formed on the intermediate layer, The intermediate layer comprises inorganic particles, conductive materials and bonding materials. The inorganic particles are hydroxides containing metal elements other than alkali metals and alkaline earth metals, and further containing at least one of 0.001 to 2 mass % of alkali metals and 0.1 to 4 mass % of alkaline earth metals.
6. The positive electrode for a secondary battery according to claim 5, wherein The inorganic particles contain alkali metal and alkaline earth metal. 7 . A secondary battery comprising the positive electrode for a secondary battery according to claim 5 or 6 , a negative electrode, and an electrolyte.
8. A positive electrode for a secondary battery, comprising a current collector, an intermediate layer formed on at least one surface of the current collector, and a composite material layer formed on the intermediate layer, The intermediate layer comprises inorganic particles, conductive materials and bonding materials. The inorganic particles are composed of a metal compound including a metal other than an alkali metal and an alkaline earth metal, and the metal compound contains 0.1 to 2% by mass of an alkali metal and 3 to 4% by mass of an alkaline earth metal.
9. The secondary battery positive electrode according to claim 8, wherein: The metal compound is at least one selected from metal oxides and metal hydroxides.
10. The positive electrode for a secondary battery according to claim 8, wherein The metal compound contains at least one selected from the group consisting of manganese oxide, silicon dioxide, titanium dioxide, aluminum oxide, aluminum hydroxide and boehmite as a main component. 11 . A secondary battery comprising the positive electrode for a secondary battery according to claim 8 , a negative electrode, and an electrolyte.
12. A positive electrode for a secondary battery, comprising a current collector, an intermediate layer formed on at least one surface of the current collector, and a composite material layer formed on the intermediate layer, The intermediate layer comprises inorganic particles, conductive materials and bonding materials. The inorganic particles are composed of a metal compound having at least one selected from manganese oxide, silicon dioxide, and titanium dioxide as a main component, containing 0.001 to 2 mass % of sodium, and containing no alkaline earth metal. 13 . A secondary battery comprising the positive electrode for a secondary battery according to claim 12 , a negative electrode, and an electrolyte.
Citation Information
Patent Citations
Positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery
JP2016127000A
Positive electrode for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
CN105742573A
Alumina, slurry comprising the same, alumina porous film using the same, multilayer separator, nonaqueous electrolyte secondary battery, and method for producing nonaqueous electrolyte secondary battery
JP2018138509A